Detection of Neutralizing Anti‐Type 1 Interferon Autoantibodies. Issue 8 (17th August 2022) - Shaw, Elana R.; Rosen, Lindsey B.; Ding, Li; Holland, Steven M.; Su, Helen C.
Abstract: Autoantibodies (autoAbs) that neutralize type 1 interferons (T1IFNs) are a major risk factor associated with developing critical COVID‐19 disease and are most commonly found in individuals over age 70 and in patients with genetic or acquired thymic defects. Swift identification of autoAb‐positive individuals may allow targeted interventions to prevent critical COVID‐19 disease. Herein, we provide a workflow and protocols aimed at rapidly identifying individuals who are autoAb positive from a large cohort. Basic Protocol 1 describes a multiplex particle‐based assay to screen large cohorts of individuals for binding levels of anti‐T1IFN autoAbs, and Basic Protocol 2 describes a functional assay to test if autoAbs in patient plasma can block T1IFN‐induced JAK/STAT signaling. © Published 2022. This article is a U.S. Government work and is in the public domain in the USA. Basic Protocol 1 : Multiplex particle‐based bead assay to screen for binding levels of anti‐type 1 interferon autoantibodies Alternate Protocol : Multiplex particle‐based bead assay to screen for binding levels of anti‐type 1 interferon immunoglobulin subtypes and isotypes Support Protocol : Coupling type 1 interferons (IFN‐α, IFN‐β, and IFN‐ω) to magnetic beads Basic Protocol 2 : pSTAT1 functional assay to test for neutralization activity of anti‐type 1 interferon autoantibodies